PERILAKU KERJA PENGRAJIN TENUN TRADISIONAL: KASUS DI DESA SILUNGKANG - Siburian, Robert (P2KK LIPI, 2000)
This article describes the behaviour of textile entreprises in Silungkang, West Sumatra. These textile entreprises have been developing for a long time and still exist up to present. The Silungkangs are famous among the Minangkabau ethnic group, but they do not have a cooperative spirit. They work individually, and are difficult to trust other people outside they. They would nOl receive any information from outside ,even it is for their own sake of business. This individualistic behaviour is called in Minangkabau 'galir'.